On the food and feeding habit of an estuarine catfish (Mystus gulio Hamilton) in the south-west coast of Bangladesh (University Journal of Zoology, Rajshahi University, 2009)
No Abstract doi:10.3329/ujzru.v27i0.1962 Univ. j. zool. Rajshahi Univ. Vol. 27, 2008 pp. 91-94